1985
DOI: 10.1063/1.96079
|View full text |Cite
|
Sign up to set email alerts
|

Ion implant monitoring with thermal wave technology

Abstract: A new method, based on thermal wave technology, is used to monitor the ion implantation process in silicon. It is a noncontact, nondestructive technique that requires no special sample preparation or processing, has high sensitivity even at low dose, and provides a one-micron spatial resolution capability. This method allows, for the first time, the ability to monitor the critical ion implantation process directly on the patterned product integrated circuit wafers as well as on the usual test wafers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…The thermal waves provide information about the local thermal transport properties while the plasma waves provide information about the local charge carrier transport properties. It is this latter sensitivity to local electrical properties that accounts for the success of the modulated reflectance method as a process control tool in the semiconductor industry for monitoring ion implant dose levels [4,5) and plasma-induced damage effects [6,7) in Si wafers.…”
Section: Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal waves provide information about the local thermal transport properties while the plasma waves provide information about the local charge carrier transport properties. It is this latter sensitivity to local electrical properties that accounts for the success of the modulated reflectance method as a process control tool in the semiconductor industry for monitoring ion implant dose levels [4,5) and plasma-induced damage effects [6,7) in Si wafers.…”
Section: Semiconductorsmentioning
confidence: 99%
“…The thermal waves provide information about the local thermal transport properties while the plasma waves provide information about the local charge carrier transport properties. It is this latter sensitivity to local electrical properties that accounts for the success of the modulated reflectance method as a process control tool in the semiconductor industry for monitoring ion implant dose levels [4,5) and plasma-induced damage effects [6,7) in Si wafers.In these applications no attempt is made to perform thermal wave imaging of individual defect structures in the silicon wafer. Recently we have demonstrated that the modulated reflectance method can be used to image localized defects and structures by employing high-density raster scanning techniques [8].…”
mentioning
confidence: 99%
“…The imaging system used in these experiments is a thermal wave modulated reflectance/deflection instrument similar to the one we developed for ion implant process control [1][2][3][4]. In this imaging system the sample is rapidly scanned in an x-y raster beneath the stationery pump and probe laser beams in 0.4jlm steps.…”
Section: Imaging Systemmentioning
confidence: 99%
“…As described in [13][14][15][16], the effects of the thermal and plasma waves on the reflectivity of silicon result in a net modulated reflectivity signal that is very sensitive to the presence of disorder or defects in the surface region of the wafer. The measurement method is similar to that employed for ion implant monitoring [17,18] and polishing damage characterization [12] in which damage to the silicon is detected by the Therma-Probe system. Significant characteristics of this method are the use of low-power laser beams for noncontact, nondestructive IOOasurements, the use of al-micron probe spot allowing measurements to be made on pattemed, product wafers as well as tes t wafers, the speed of the measurements (3-7 minutes) and the high sensitivity allowing extremely low levels of damage to be measured.…”
Section: Evaluation Techniquementioning
confidence: 99%